2016
DOI: 10.18203/issn.2455-4510.intjresorthop20162617
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical comparison of two cephalomedullary nails; one using a single lag screw with antirotator blade and a nail using two lag screws for unstable intertrochanteric fractures

Abstract: <p class="abstract"><strong>Background:</strong> Implant choice for fixation of intertrochanteric fractures remains controversial despite being one of the most commonly performed operations. Although use of sliding hip screws is still considered a gold standard in treatment of these fractures, there is a wide tendency in using cephalomedullary nails because of their biomechanical superiority over sliding hip screws. This trial was initiated in order to compare the biomechanical properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…9 Subsequently, a study performing a biomechanical comparison reported that A-PFN reduced lag screw cut-out issues. 10 In our study, both A-PFN and A-DHS have a single lag screw, the additional wedge with rail system ensures anti-rotation, and the system entails three different compression parts. Proximal femoral nail antirotation (PFNA), a third generation nail, contains a helical head that increases trabecular bone volumetric compression in osteoporotic fractures, decreasing cut-out rate.…”
Section: Resultsmentioning
confidence: 86%
“…9 Subsequently, a study performing a biomechanical comparison reported that A-PFN reduced lag screw cut-out issues. 10 In our study, both A-PFN and A-DHS have a single lag screw, the additional wedge with rail system ensures anti-rotation, and the system entails three different compression parts. Proximal femoral nail antirotation (PFNA), a third generation nail, contains a helical head that increases trabecular bone volumetric compression in osteoporotic fractures, decreasing cut-out rate.…”
Section: Resultsmentioning
confidence: 86%